Influence and persuasion : (Harvard Business Review Press, 2018)
Changing hearts is an important part of changing minds. Research shows that appealing to human emotion can help you make your case and build your authority as a leader. This book highlights that research and shows you how to act on it, presenting both comprehensive frameworks for developing influence and small, simple tactics you can use to convince others every day.